Experiments and modeling of the thermo-mechanically coupled behavior of VHB. (1st May 2022) - Alkhoury, Keven; Bosnjak, Nikola; Wang, Yueping; Lee, Howon; Nadimpalli, Siva; Chester, Shawn A.
Abstract: Temperature is well known to have a significant effect on the overall mechanical performance of viscoelastomers. In this work, we investigate the thermo-mechanically coupled behavior of VHB 4910 using a combined experimental and modeling approach. We first characterize the material behavior by performing a set of large deformation uniaxial experiments at different temperatures. We then model the observed thermo-mechanical behavior and calibrate that model to the uniaxial experiments. Lastly, the model is implemented as a user material subroutine in a finite element package for validation purposes. A key finding of this work is that while increasing the temperature stiffens the elastic contribution, it concurrently reduces the viscoelastic contribution to the overall behavior of VHB.